Here are my hands - Martin, Bill, 1916-; Archambault, John.; Rand, Ted (New York : Holt, 1987)
The owner of a human body celebrates it by pointing out various parts and mentioning their functions, from "hands for catching and throwing" to the "skin that bundles me in."
2.0
K-3
Keywords: Body, Human -- Fiction; Stories in rhyme; Stories in rhyme; Human anatomy -- Fiction